Internal and external risk based assesment and evaluation for the large infrastructure projects - Burcar Dunovic, Ivana; Radujkovic, Mladen; Vukomanovic, Mladen (Journal of Civil Engineering and Management, 2016)
The level of sensitivity to project success of large infrastructure projects is significantly greater in front-phase than in execution phase. Yet, due to focus on execution phase, methods for project assessment and on-going evaluation during front phases are insufficiently developed. On the other hand, risk management approaches has been moved from risk management towards holistic uncertainty management which is the most beneficial in front end phase of the project. This research identifies that majority of methods and techniques available does not support uncertainty management concept. The purpose of this paper is to develop and new method for risk based project assessment and evaluation integrating risk impact modelling using cumulative distribution curves (CDC) and multi-criteria project evaluation approach. Research is based on in-depth risk analysis of 15 large infrastructure projects using risk model of components and characteristics. The conclusion of the paper is verification and validation of method that combines qualitative and quantitative analysis using risk components, risk breakdown structure, AHP method and risk impact modelling using cumulative distribution curves (CDC) for internal and external risk based assessment and evaluation of large infrastructure projects.